1976
DOI: 10.1017/s000156600001388x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Ovulation and Monozygotic Twinning

Abstract: Aiming to show that delayed ovulation may induce MZ twinning, follicular maturation was induced in the rabbit by a small quantity of Pregnant Mare Serum Gonadotropin (16 UI four times): coitus, which induces ovulation in the rabbit, was delayed 60 hours after the last injection. From the 387 blastocysts obtained after this treatment, 6 (1.5%) were pairs of MZ twins, twinning being otherwise exceptional in the rabbit. Other anomalies were shown by the embryos, apparently related to a deficient quality of the eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…1995), as in rabbit and pig (Ashworth et al . 1998; Bomsel‐Helmreich & Papiernik‐Berkhauer 1976). McLaren et al .…”
Section: Early Origins Of Individualitymentioning
confidence: 99%
See 1 more Smart Citation
“…1995), as in rabbit and pig (Ashworth et al . 1998; Bomsel‐Helmreich & Papiernik‐Berkhauer 1976). McLaren et al .…”
Section: Early Origins Of Individualitymentioning
confidence: 99%
“…However, the impact of twinning may depend on the frequency of natural MZs in experimental animals. Lack of genetic markers constrains studies in genetically inbred species; best estimates are that natural MZ twinning is very rare in mice (McLaren et al 1995), as in rabbit and pig (Ashworth et al 1998;Bomsel-Helmreich & Papiernik-Berkhauer 1976). McLaren et al (1995) reported less than five identical pairs from over 2000 mice born.…”
Section: Non-hormonal Communication: Twin Effectsmentioning
confidence: 99%
“…Thus, in animal models, delayed implantation of the embryo is associated with polyembryony in armadillos, while delayed ovulation, frequently occurring in the first cycle after withdrawal of oral contraceptives, 14 induces monozygotic twinning in rabbits. 15 In Brazil, the hormone treatment on women to induce ovulation, whether followed by in vitro fertilization or not, is mostly performed in private clinics. Therefore, it is a reasonable supposition that women with a high standard of life attended at private hospitals would include a high proportion of those who have had assisted fertilization, which is associated with multiple births.…”
Section: Introductionmentioning
confidence: 99%
“…(16) Finally, as in lower vertebrates, an association between twinning or partial axial duplication and aging or ''overripening'' of oocytes has been observed in mammals. (17)(18)(19) Figure 1. Bisections to produce mouse zygotes that lack animal (A) or vegetal (B) polar regions and corresponding controls (C).…”
Section: Why the Issue Is Still Openmentioning
confidence: 99%